2017
DOI: 10.1111/fme.12241
|View full text |Cite
|
Sign up to set email alerts
|

Recreational fisheries in Portofino Marine Protected Area, Italy: Some implications for the management

Abstract: Since the 1970s, recreational fishing has become a mass hobby in Italy, reaching a large number of people, who, using modern equipment, increased their harvesting capacity, provoking serious conflicts with the professional fisheries. Recreational fishing is strictly regulated inside Italian Marine Protected Areas (MPAs) and is generally allocated to local residents, mainly to reduce the tensions caused by limitations of access to the resources. The aim of this study was to provide an analysis of recreational f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 29 publications
0
10
1
Order By: Relevance
“…Pleasure crafts could be allowed to moor to buoys installed for this purpose, which would be especially useful for diving centres: if correctly managed, scuba‐diving tourism represents a sustainable activity that generates revenue and supports local communities (Lucrezi et al, ), and may even actively support conservation (Cerrano, Milanese, & Ponti, ). Inspections in 2016 showed that derelict fishing gear caused a severe impact on epibenthic communities, suggesting that all forms of bottom fishing must be banned and recreational fishing should be strictly regulated (Venturini, Campodonico, Cappanera, Fanciulli, & Cattaneo‐Vietti, ).…”
Section: Discussionmentioning
confidence: 99%
“…Pleasure crafts could be allowed to moor to buoys installed for this purpose, which would be especially useful for diving centres: if correctly managed, scuba‐diving tourism represents a sustainable activity that generates revenue and supports local communities (Lucrezi et al, ), and may even actively support conservation (Cerrano, Milanese, & Ponti, ). Inspections in 2016 showed that derelict fishing gear caused a severe impact on epibenthic communities, suggesting that all forms of bottom fishing must be banned and recreational fishing should be strictly regulated (Venturini, Campodonico, Cappanera, Fanciulli, & Cattaneo‐Vietti, ).…”
Section: Discussionmentioning
confidence: 99%
“…The impacts of recreational and illegal fishing for the future of commercial fisheries are therefore extremely significant, especially as illegal fishers are rapidly improving their fishing techniques to catch more valuable fish at relatively low cost. For instance, using new artificial baits, such as jigs, that seem to increase the catchability of vulnerable species such as the Dentex dentex (Lloret et al., ; Venturini et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…They require low capital investment, using a wide range of fishing gears, allowing multi‐specific and seasonal catches (Farrugio, Oliver & Biagi, ; Freire & Garcı́a‐Allut, ; Forcada, Valle, Sánchez‐Lizaso, Bayle‐Sempere & Corsi, ; Guyader et al., ; Halouani, Ben Rais Lasram, Khalfallah, Zeller & Pauly, ). Concomitantly, the increase in human populations inhabiting coastal areas can contribute to an increase in the practice of recreational fishing, which is recognised as one of the most common leisure activities (Arlinghaus et al., ; Venturini, Campodonico, Cappanera, Fanciulli & Cattaneo Vietti, ). Recreational fishing (REC) is defined as all fishing activities that are not conducted for commercial or subsistence purposes (Pawson, Glenn & Padda, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last 18 years of protection, fish biomass in Portofino MPA certainly increased, showing an average value of 17.5 kg/125 m², among the highest recorded inside the Italian MPAs (Guidetti et al, 2015). This status generates a positive spill over effect, but attracted a number of anglers who could fish about 3 t/year, corresponding up to the 5% of the total annual local artisanal yield (Venturini et al, 2017). However, these data have to be considered as rough estimates, because the final harvesting is certainly influenced by the real potential of the area in terms of catchable biomasses, by the fishing ability of the single angler as well as by his honesty in providing data.…”
Section: Introductionmentioning
confidence: 99%